The nexus between vulnerability and criminality: experiences of foreign nationals in South Africa - Shandré Kim Jansen van Rensburg (Cogent Social Sciences, 2024)
In South Africa, there is an ongoing increase in the migration of foreign nationals seeking economic opportunities due to instability in neighbouring African nations. While offering prospects for advancement, some of these foreign nationals face vulnerability to victimisation and criminality. Despite growing research interest, studies addressing the link between vulnerability and criminality among foreign nationals in South Africa are lacking. The potential ramifications of neglecting this nexus can result in community conflict, diplomatic strains, and economic and regional turbulence. Thus, this paper explores the nexus between vulnerability and criminality experienced by low-income foreign nationals living in South Africa. The paper’s findings are informed by a qualitative inquiry into the experiences of 15 foreign nationals living in South Africa. Data was collected through one-on-one interviews and were analysed thematically. The findings detail how vulnerability and criminal behaviour intersect among low-income foreign nationals regarding bribery, corruption and illegal survival strategies. Through the participants’ voices, their unique challenges and risks are illuminated. Additionally, peacekeeping strategies in South Africa and Africa are informed by understanding the socio-economic factors contributing to their vulnerability. These include community engagement initiatives, specialised training for government officials, stricter proctoring measures, legal support and advocacy and sophisticated cross-border cooperation.